Early performance of cocoa (Theobroma cacao L.)genotypes in arecanut under Assam condition of North Eastregion of India - Singh, L.S.; Uchoi, Anok; Acharya, G.C.; Apshara, S. Elain; Das, Alpana (Journal of Plantation Crops, 2021)
Cocoa is an important plantation crop grown in southern parts of India. Though many cocoa varieties have been released for cultivation in different parts of India, there is no variety recommended for cultivation exclusively for India’s North East region, especially Assam, where arecanut is grown as an important cash crop. Therefore the present investigation was undertaken to study the performance of twelve cocoa genotypes for its growth, pod yield and yield attributing traits for subsequent research programmes. The data for growth, pod yield and yield attributing traits were recorded three years after planting for five years (2015 to 2019), and the mean data were used for analysis. Genotype VTLC 11 significantly produced greater plant height (2.70 m), stem circumference (27.73 cm), height at jorquetting (36.16 cm) and canopy area (17.00 m2). Mean average pod yield among the genotypes varied from 20.65 to 48.40 tree-1 year-1. Genotype VTLC 19 produced significantly higher pod yield (48.40), number of fresh beans pod-1 (34.06), fresh bean weight pod-1 (229.65 g), dry bean weight pod-1 (119.32 g), single dry bean weight (1.20 g) and dry bean yield (1.76 kg). Considering the most economic traits of cocoa, VTLC 19 appears to be the most suitable genotype for commercial cultivation in the region.